2017
DOI: 10.13189/ujer.2017.051115
|View full text |Cite
|
Sign up to set email alerts
|

The Opinions of the Turkish Teacher Candidates about the Webquest

Abstract: Webquest, first introduced by Dodge in 1995, is a research and inquiry tool that uses the Internet as a resource. The interest of the students regarding the characteristics is included in the related literature according to the researches made. There is a need for studies to be regarded by the teacher candidates for the webquests regarded by the teachers and students. The purpose of this research is to determine the opinions of Turkish teacher candidates who have knowledge about Webquest and have designed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Like Almalı (2020) and Hoy (2016), this study found that using Web 2.0 tools was positively associated with students' attitudes toward English lessons and therefore a contributing factor for academic success. Similarly, Akçay and Şahin (2012) investigated how Webquest, a Web 2.0 tool that they used, affected the Turkish course's success as well as the attitudes of students towards it, and their findings coincide with those of this study, which indicates that the Web 2.0 tool used high academic achievement as well as student attitudes toward the course. Cunningham (2015) conducted a study to evaluate the effectiveness of the Voki Web 2.0 tool in an online writing course with 40 students.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 79%
“…Like Almalı (2020) and Hoy (2016), this study found that using Web 2.0 tools was positively associated with students' attitudes toward English lessons and therefore a contributing factor for academic success. Similarly, Akçay and Şahin (2012) investigated how Webquest, a Web 2.0 tool that they used, affected the Turkish course's success as well as the attitudes of students towards it, and their findings coincide with those of this study, which indicates that the Web 2.0 tool used high academic achievement as well as student attitudes toward the course. Cunningham (2015) conducted a study to evaluate the effectiveness of the Voki Web 2.0 tool in an online writing course with 40 students.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 79%